O professor bilíngue e o intérprete em Libras no ensino de Geografia - Alves, Ivo Dias [UNIFESP] (2020)
This research is part of challenging instances for the teaching of Geography, for this it was developed based on two distinct contexts: on the one hand, a regular school with an inclusive perspective, in which deaf students and listeners are inserted in the same classroom and class, with the mediation of a Brazilian Sign Language interpreter (Libras) for the translation and interpretation of classes; on the other, a bilingual school for the deaf, in which the teacher teaches in Libras. To this end, we proposed, as general objective to investigate how geography teaching has been developed in two schools in which there are deaf students enrolled: a Municipal School of Bilingual Education (EMEBS) and a State School of Inclusive Perspective (EERI). As Specific objectives we proposed to understand how the relationship of teachers (listeners) and interpreters of Libras with students (deaf) in the teaching of Geography takes place; know what materials, practices and didactics are used by teachers in teaching Geography to deaf students; understand the importance of teaching Libras in geography degrees. Although this work reinforces that the mastery of Libras and the content taught in geography classes are essential for knowledge about human space and its forms of transformation and occupation, we observe, among other final considerations, that, on the one hand, in the EERI, the deaf student is encouraged to read and interpret as a listener, even having an interpreter in the room. Thus, the presence of the interpreter is inefficient, since those involved are not in a visual environment. In EMEBS, on the other hand, the speech and activities presented by the collaborator reinforce that teaching is not only in the set of activities, but also in the visual form, which is suitable for the spatial and geographical formation of deaf students.